Reproductive calendar of the Embera Eyabida indigenous groups from the Nusidó community in Frontino, Colombia (2014)
ABSTRACT: Objective. This work sought to characterize the calendar, pressure, and reproductive intensity of the Embera eyabida Indians from Nusidó. Methodology. Through the female reproductive history technique, aimed at women older than 10 years of age from Nusidó during 2011, information was gathered from 63 participants. Said women represent 76% of the total of those older than 10 years of age. Results. The reproductive calendar is characterized by a mean age of menarche of 12 years and a mean entry into conjugal union of 14.4 years with an interval of less than one year for the start of the first gestation. The average of the intergenesic intervals was 29.3 months; these are short in 41.9% of the women, medium in 54.8% and above 60 months in 3.2%. Findings include: a medium and lower Reproductive Stress Index (RSI) in 71.4% of the women and a Reproductive Rate (RR) between medium and high in 19.0% of the women. Conclusion. Although early ages are observed in various parameters of the reproductive life, the results permit identifying changes in the indigenous people from Nusidó with respect to prior studies for the ethnic group and the subgroup; among these, there are: improved access to female literacy, delay in the entry into the union, and the start of maternity in young women.